The Effect of Work Environment, Organizational Commitment and Competence on Employee Performance at UPTD Puskesmas Abang II - Arthawan, I Ketut Agus Muliadi; Terimajaya, I Wayan; Budi Artha, I Wayan; Thelma, Chanda Chansa (Management Department Universitas Islam Negeri Sumatera Utara, 2025)
This study investigates employee performance in public health services at the community health center level, focusing on how internal and external factors shape outcomes. Using a quantitative approach, it explores whether organizational commitment mediates the impact of the work environment and competence on performance. The research surveyed all 64 staff at UPTD Puskesmas Abang II, collecting data through carefully tested questionnaires. Analysis included reliability, validity, classical assumption checks, and path analysis. Key findings reveal that a supportive work environment and higher competence both significantly strengthen organizational commitment. Additionally, the work environment and competence each directly enhance employee performance, while organizational commitment independently boosts performance levels. However, organizational commitment does not mediate the relationship between the work environment or competence and performance. This suggests that although commitment is beneficial, it does not serve as a connecting pathway in this context—possibly due to factors like work stress, organizational culture, or heavy workloads. The study highlights the importance of managerial efforts to align employee values with organizational goals, foster motivation, and deepen commitment to ensure sustained improvements in employee performance. Keywords: Put your keywords here, keywords are separated by comma. We would like to encourage you to list your keywords in this section